The Language of Ethics and Double Standards in the Affective and Sexual Socialization of Youth. Communicative Acts in the Family Environment as Protective or Risk Factors of Intimate Partner Violence - Rios-González, Oriol; Peña Axt, Juan C.; Duque Sánchez, Elena; De Botton Fernández, Lena (Frontiers in Sociology, 2018)
One of the explanatory factors for the perpetuation of intimate partner violence (IPV) is the socialization process. There is broad literature on the role of family in socializing gender roles and the influence on reproducing IPV. However less research has been developed on the effects of communicative acts in the family environment as a protective or risk factor in front of IPV. This article presents sound evidence confirming the presence of language of ethics that is reproducing stereotyped models of attraction in heterosexual relationships, which empties good people of attractiveness and indirectly contributes to maintain the link between desire and aggressiveness. The language of ethics is characterized by integrating speech acts that exclusively include ethics and exclude desire when talking about egalitarian boys or men. To analyze this reality, a qualitative study has been conducted framed in the communicative methodology. This methodology has been recommended by the European Commission to conduct research on vulnerable groups and social inequalities, which has the aim to advance knowledge on social transformation. Drawing on this approach, three different data-collection techniques have been implemented: in-depth interviews, daily-life stories and focus groups. The fieldwork includes a sample of 52 young men and women between the ages of 18 and 23 from a vocational training high school, and 4 fathers and 4 mothers of some of these young people. The findings confirm the existence of a model of socialization that replicates family relations based on the maintenance of the double standards. Thus, mothers used to employ the language of ethics with their daughters fostering a controversial effect, that is, the latter prefer to start affective and sexual relationships with boys who are aggressive and not egalitarian. On the other hand, fathers used to employ language of desire with their sons stimulating the performance of chauvinist behaviors that denigrate women and girls.